Relationship Between Body Mass Index and Skinfold Thickness with Blood Pressure in Medical Students - Salma Arini Putri; Choesnan Effendi; Asami Rietta Kumala (Health Notions, 2019)
The prevalence of obesity in women in Indonesia is increasing. Obesity is characterized by excess BMI and fat mass in the body. High body fat mass is associated with metabolic diseases and blood pressure (BP). The research design was cross-sectional, involved the students of the Faculty of Medicine, Universitas Hang Tuah Surabaya in July 2019. Sampling was done using stratified random sampling with 48 female volunteers who were grouped into 16 volunteers each semester. In students of Semester II, the average BMI was 21.2±2.4 kg/m2, Skinfold Thickness (SFT) 54.6±9.9 mm, BP 109±9.6/71±8.3 mmHg. In students of Semester IV, the average BMI was 23±3.5 kg/m2, SFT 48±14.10 mm, BP 109±9.7/77±7 mmHg. In students of Semester VI, the average BMI was 24.33±4.72 kg/m2, SFT 69.87±21.54 mm, BP 122±8.9/84±11mmHg. The correlation coefficient of SFT and Systolic Blood Pressure (SBP) was 0.697, SFT and Diastolic Blood Pressure (DBP) was 0.362, BMI and SBP was 0.355, while BMI and DBP 0.171. There was a correlation between SFT and SBP and DBP, BMI and SBP in female students of semester II, IV and VI. Keywords: skinfold thickness (SFT); body mass index; blood pressure